D-lactic acid production from hydrothermally pretreated, alkali delignified and enzymatically saccharified rockrose with the metabolic engineered Escherichia coli strain JU15 - Fernandes, M. C. (2022)
ABSTRACT: Rockrose lignocellulosic residues (RR) were selectively fractionated for hemicellulose separation using autohydrolysis, followed by an alkaline treatment to solubilize the lignin. The cellulose-enriched solids were used to study the effect of solid loading (SL: 2-10%) and enzyme dosage (ED: 6.34-23.66 FPU/g dry biomass) on saccharification using a Doehlert experimental design, followed by fermentation with the metabolic engineered Escherichia coli strain JU15 to produce D-lactic acid (DLA). Pretreatment increased glucan content and enzymatic digestibility up to 84%. A significant positive effect of SL and ED was found for glucose production, but SL negatively impacted glucose yield. DLA concentrations and productivity varied from 8.85 to 32.98 g/L and 1.11 to 2.17 g/(Lh), respectively. Overall process efficiency strongly depended on saccharification yield and varied from 33 to 71%. These results indicate that sequential autohydrolysis, delignification, and fermentation of RR may be a potential relevant strategy for D-lactic production in the biorefinery framework.